Analysis of Factors in Improving The Competitiveness of Small And Medium Industries of Songket Cloth Traditional Weaving - Yudha Agil Prasetya Effendi; Deassy Apriani (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
ABSTRACTSmall and medium industries are the foundation for expanding employment and employment to improve the economy. Of course, the increase or development of the number of small and medium industries will continue to increase if the products produced can survive market competition both locally and outside the region. One of the small and medium industries is the traditional weaving craft industry and songket. This study analyzes factors in increasing the competitiveness of small and medium industries of songket cloth weaving in Ogan Ilir Regency. Data taken directly from 50 samples of the songket fabric custom weaving industry were analyzed using multiple linear regression. The results of this study show that simultaneously, the availability of capital, labor, productivity, product differentiation and marketing distribution have a significant effect on competitiveness. While partially, the availability of capital, labor, productivity, product differentiation has a significant effect on competitiveness, except for insignificant marketing distribution.Keywords : Competitiveness, Indigenous Weaving and Songket Handicraft Industry, Small and Medium Industry